Four Women: The E. Cassirer’s Theory and Its Analytical Potential for Understanding Iraqi Symbolic Painting by J. Saleem (Al-Academy, 2023)
Based on the theoretical ideas of E. Cassirer, a methodology is developed and an analysis of the painting work by J. Saleem, a representative of modern Iraqi painting, is carried out. While comparing the artistic programme of J. Saleem and the views of E. Cassirer, the methodological potential of the theory of the symbol for the art criticism analysis of the regional painting is clarified. Comparative analysis with the inclusion of the works of B. Buffet, B. Turetsky, J. Miro helps to see the multiple meanings of the same cultural symbol in thematically similar works of different years, created in different socio-cultural circumstances. The article shows that for regions with a shorter history (France, Russia, Spain, etc.), which have lost direct connection with the original myths in the process of civilization development, E. Cassirer's methodology can be applied only with significant amendments.